Low cholesterol levels are associated with a high mortality risk in older adults without statins therapy: An externally validated cohort study. (September 2020) - Turusheva, Anna; Vaes, Bert; Degryse, Jean-Marie; Frolova, Elena
Highlights: A U-shaped association between total cholesterol (TC) level and all-cause mortality was detected. The TC level range associated with the lowest mortality was 5.4–7.2 mmol/L. The association between low TC levels and a higher risk of all-cause mortality was externally validated in a Belgian cohort. Abstract: Background: The relationship of total cholesterol (TC) levels with mortality among older adults without statin therapy has not been fully studied. Aims: To examine the relationship between TC and all-cause mortality in adults aged 65 years and older in Russia without statin therapy. Methods: This was a population-based prospective cohort study of community-dwelling people aged 65 years and older in Russia. Data from 379 individuals on cardiovascular risk factors; comorbidities; cognitive, physical and autonomous function; lipid panel; B-type natriuretic peptide; C-reactive protein; and others were collected through interviews, clinical examinations, and laboratory tests. The total follow-up time was 3 years. Cox proportional hazards models for all-cause mortality, C-statistics, internal validation and external validation using the Belgian population from the BELFRAIL study were performed. Results: A U-shaped association between the TC level and all-cause mortality was identified. Older adults without statin therapy and with low/high TC levels were at higher risk for mortality even after adjustment for covariates, with a hazard ratio (HR) of 5.78 (1.96–17.03) for TC < 5.4 mmol/L and an HR of 6.24 (1.69–22.94) for TC levels > 7.2 mmol/L. The association between low TC and all-cause mortality was confirmed in an external population of adults 80 years and older. Conclusion: The TC level range associated with the lowest mortality was 5.4–7.2 mmol/L, irrespective of concomitant diseases or health status. The association between low TC levels and a high risk of all-cause mortality was confirmed in a Belgian cohort of adults 80 years and older.